2007
DOI: 10.1038/sj.onc.1210920
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells share molecular signature with mesenchymal tumor cells and favor early tumor growth in syngeneic mice

Abstract: Tumor microenvironment in carcinomas recruits mesenchymal cells with an abnormal proangiogenic and invasive phenotype. It is not clear whether mesenchymal tumor cells (MTCs) derive from the activation of mature fibroblasts or from their stem cell precursors. However, stromal cell activation in tumors resembles in several aspects the mesenchymal rearrangement which normally occurs during reparative processes such as wound healing. Mesenchymal stem cells (MSCs) play a crucial role in developmental and reparative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
3
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(77 citation statements)
references
References 45 publications
3
68
3
3
Order By: Relevance
“…This notion also appears to be supported by several studies showing antitumor effects of MSCs [8][9][10]. In contrast, others reported that MSCs could promote tumor progression or metastasis in animal models [11][12][13]. Thus, it is still unclear, regarding the pro-or anti-cancer role of MSCs, in particular the effects in patients [14].…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…This notion also appears to be supported by several studies showing antitumor effects of MSCs [8][9][10]. In contrast, others reported that MSCs could promote tumor progression or metastasis in animal models [11][12][13]. Thus, it is still unclear, regarding the pro-or anti-cancer role of MSCs, in particular the effects in patients [14].…”
Section: Introductionmentioning
confidence: 54%
“…Several studies demonstrated anti-tumor effects [8][9][10] whereas others showed tumor promoting effects [11][12][13] of MSCs in different tumor models. Regarding the effects on CRC, most of the studies have shown a pro-cancer effect of MSCs [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…The resulting remodeling of the ECM, which the mesenchymal tumor cells execute, is an integral component of cancer progression [83,88,89] . There is evidence for epigenetically altered MSC cells driving both cancer initiation and progression [80,90,91] . The secretion of angiogenic and anti-apoptotic factors by MSC, as well as their ability to suppress T cellmediated immune response has been proposed to account for the tumor-supporting role of MSC [37,42,79] .…”
Section: Mesenchymal Stromal Cells and Cancer Progressionmentioning
confidence: 99%
“…Recruitment of experimentally administered MSC by tumors has been demonstrated in animal models [78,79] . It has been proposed that MSC may be the progenitors of tumor stromal cells, which are also 百世登 Baishideng TM© WJSC|www.wjgnet.comtermed tumor-associated (or cancer-associated) fibroblasts (CAF) [78,[80][81][82][83] . Upon tumor infiltration, MSC may re-establish the trophic microenvironment they normally maintain in the bone marrow [84,85] .…”
Section: Mesenchymal Stromal Cells and Cancer Progressionmentioning
confidence: 99%
“…But animal experiments showed that MSCs can actually promote tumor growth in vivo when they are co-injected into immunodeficient mice with tumor cells. A few similar reports indicated that MSCs can promote the growth or early appearance of B16 melanoma, 19 human bone marrow and colon cancer, 20 and carcinoma-derived mesenchymal tumor 21 in vitro and/or in animals. It is speculated that the tumor growth enhancement is due to MSCs' immunosuppressive effects mediated by MSC-secreted cytokines, such as hepatocyte growth factor and transforming growth factor-β1, and their ability to form a cancer stem cell niche that facilitates tumor cell growth in vivo.…”
mentioning
confidence: 99%